DIVERSIFIKASI KONSUMSI MASYARAKAT LOKAL - Umanailo, M. Chairul Basrun (Jurnal AGRISEP, 2019)
The research was conducted in Waimangit Village of Buru Regency with the objectives to analyze community food security planning, make projections for diversification of local food consumption and food security in Waimangit Village. The approach used is qualitative with the basic method of descriptive analysis. The results showed that, Local food consumption is still low with the level of diversification of food consumption is also still low, factors that affect the level of diversification of food consumption is; expertise in processing, number of household members and social interaction, There is no shift of rice consumption pattern to local food, local food consumption condition only occurs at certain age segmentation, Food security level generally belong to food vulnerable where household is long term plant based farmer.